Aqua Mediated Synthesis of Bio-active Compounds - S. Panda, Siva (Mini Reviews in Medicinal Chemistry, 2013)
Recently the aqueous medium has attracted the interest of organic chemists, and many. Moreover, in the past 20 years, the drug-discovery process has undergone extraordinary changes, and high-throughput biological screening of potential drug candidates has led to an ever-increasing demand for novel drug-like compounds. Noteworthy advantages were observed during the course of study on aqua mediated synthesis of compounds of medicinal importance. The established advantages of water as a solvent for reactions are, water is the most abundant and available resource on the planet and many biochemical processes occur in aqueous medium. This review will focus on describing new developments in the application of water in medicinal chemistry for the synthesis of bio-active compounds possessing various biological properties.
Keywords: synthesis